Hubungan Pemberian Asi Eksklusif Dengan Kejadian Pneumonia Pada Balita Di Wilayah Kerja Puskesmas Pedan Klaten - Choyron, Via Al Ghafini, Bejo Raharjo, SKM, M.Kes, Kusuma Estu Werdani, SKM., M.Kes (2015)
Pneumonia is one of the causes of morbidity and mortality in infants, caused by microorganisms such as Streptococcus pneumoniae, Streptococcus Aures, Haemophyllus influenza, Escherichia coli and Pneumocystis jirovenci. The purpose of this study was to analyze the relationship between exclusive breastfeeding with the incidence of pneumonia in infants in Puskesmas Pedan Klaten. This type of research was observational research with case control design. Population of cases in this study was that children aged 6-24 months were recorded in the registration Puskesmas Pedan Klaten in January-June 2015, while the control population is children who did not have a history of pneumonia in Puskesmas Pedan Klaten area. Selection of the sample in the case group of 40 people and control as many as 40 people by using simple random sampling technique while using a statistical test Chi Square test. The results showed that infants who were not exclusively breastfed for 25 (62,5%) in the case group and 14 (35%) in the control group. Statistical test results showed that exclusive breastfeeding is had relationship with the incidence of pneumonia in infants in Puskesmas Pedan Klaten area (p = 0.004 ; OR = 3.095 ; 95 % CI = 1.243 to 7.706).